2010
DOI: 10.1677/joe-10-0170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adiponectin on human trophoblast invasion

Abstract: Adiponectin is an adipokine with insulin-sensitizing, antiinflammatory, anti-atherogenic, and anti-proliferative effects. The expression of specific adiponectin receptors in the placenta and in the endometrium suggests a role for this cytokine in placental development, but this role has not yet been elucidated. The invasion of trophoblast cells during the first trimester of pregnancy being crucial to placentation process, we have studied adiponectin effects on human trophoblast invasive capacities. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 58 publications
3
36
0
Order By: Relevance
“…In parallel, we performed Matrigel Transwell invasion assays with the HTR-8/SVneo cells in the presence of control medium supplemented or not with adiponectin (25 ng/mL and 250 ng/mL). As previously described by our laboratory, these experiments confirmed that adiponectin (250 ng/mL) enhanced trophoblast invasion (+23%) (Benaitreau et al 2010a). …”
Section: Involvement Of Adiponectin In the Endometrial Control Of Trosupporting
confidence: 87%
See 2 more Smart Citations
“…In parallel, we performed Matrigel Transwell invasion assays with the HTR-8/SVneo cells in the presence of control medium supplemented or not with adiponectin (25 ng/mL and 250 ng/mL). As previously described by our laboratory, these experiments confirmed that adiponectin (250 ng/mL) enhanced trophoblast invasion (+23%) (Benaitreau et al 2010a). …”
Section: Involvement Of Adiponectin In the Endometrial Control Of Trosupporting
confidence: 87%
“…A growing body of evidence has highlighted adiponectin role in the establishment of a functional placenta (Benaitreau et al 2010b). Our laboratory has shown that adiponectin promotes human trophoblast invasion by enhancing MMP-2,-9 activities and downregulating TIMP-2 mRNA expression (Benaitreau et al 2010a).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…While the presence of syncytiotrophoblast adiponectin expression has been previously debated,39, 40 the present study demonstrated adiponectin expression in both syncytiotrophoblasts and decidual glands. In the in vitro model cell experiments, we also found that adiponectin was expressed in syncytial BeWo cells.…”
Section: Discussionsupporting
confidence: 46%
“…In the current study, ODN 2006 impaired the syncytialization of BeWo cells, but neither knockdown nor overexpression of adiponectin could neutralize this effect, indicating that while it can promote trophoblast syncytialization, adiponectin cannot rescue impairment of syncytialization caused by CpG ODNs or bacterial infection. Furthermore, in addition to supporting syncytialization, adiponectin can also promote the human trophoblast migration 40. However, little is known about the effect of adiponectin on trophoblast migration under infectious conditions.…”
Section: Discussionmentioning
confidence: 99%